PRAKTEK PERJANJIAN PEMBIAYAAN KONSUMEN SEPEDA MOTOR DI SURABAYA - , Dwi Leny Kartini ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research aims to observe and understand the matters underlie the consumer financing agreement and the legal status against the property rights transfer of motorcycle from consumers to the financing company if the consumer breach of contract. The research is juridical empiric that is based on the implementation in the field to obtain the primary data preceded by a normative legal research, in the form of library research to get the secondary data. The research was conducted in Surabaya City, and overall data were analyzed qualitatively. The subjects of research consisted of the Personnel of the Financing Company, Notary, and the Personnel of Fiduciary Registration Office of Department of Law and Human Rights in Surabaya City, related to the financing agreement practice and fiduciary. This research defined some samples that will taken the respondent with applying non-probability sampling, that is does not provide equal opportunities to individuals in population to be selected into the sample, by withdrawal a purposive sampling, conducted by taking subjects that are based on the specific goals. The results indicated that the reasons underlying the property right of motor vehicle was converted to the consumer name is the consideration of time and cost efficiency, more profitable either for the financing company or consumer, because it increases the competitiveness of the financing company and facilitating the consumers, and have been arranged in Law No. 22, 2009 on the Traffic and Road Transportation. The legal position of financing company if the financing agreements are burdened with fiduciary is stronger, so has the right to be prioritized over the other creditors. Conversely, if the financing agreement is not followed by the fiduciary, the creditor position is weak because it does not have the right to be prioritized, so if the consumer breach of contract then the financing company will compete with other creditors to obtain the payment.